Meritocracy in Islamic Boarding School Tradition as Talent and Performance Based Human Resource Management in Islamic Higher Education Institutions - Ahmad Dzofron Abiyyu Tsaqib Muhes; Siti Aimah (GHAITSA : Islamic Education Journal, 2026)
Meritocracy as a principle of fairness and reward for achievement is an important foundation in human resource management (HRM), and its application in the pesantren tradition contributes to strengthening management in Islamic Higher Education Institutions (PTKI). This study aims to examine how the applica-tion of meritocracy in the pesantren tradition can become a model for talent- and performance-based HRM in PTKI. The background of this study is the need for a fair and transparent HRM system to improve the quality of Islamic higher education. The research method used a qualitative approach with a case study at the Darussalam Blokagung Banyuwangi Islamic Boarding School, which is integrated with KH. Mukhtar Syafaat University. Data collection was carried out through interviews, participatory observation, and documentation, then analyzed using the Miles and Huberman interactive model. The results of the study show that meritocracy is reflected in the selection, training, and evaluation mechanisms for students through an emphasis on academic achievement, spirituality, and leadership. Integration with PTKI strengthens performance-based HR management, producing high-quality graduates. This study provides a new perspective that the pesantren tradition is relevant as a model of talent, performance, and fairness-based HR management.